Growth analysis and nutrient absortion curves of mango fruits, cultivars tommyAtkins and keith - Fallas, Róger (2009)
Fruits of mango (Tommy Atkins and Keith) were collected in different blocks of the Farm Manga Rica, Guanacaste, Costa Rica, along their development cycle during the season 2008 2009. The fruits were collected approximately every 15 days, their its dimensions (width and length), weight (wet and dry) were measured, and then the concentration of nutrients was analyzed. The mango fruit has 2 phases at its development cycle, one of expansion, which starts at the beginning of the cycle and continues until 79 days after flowering in the case of cv. Tommy Atkins, and 93 days for cv. Keith; in the follo ing p ase the fruit increases in weig t. Absorption curves for macro and micro nutrients were obtained, and the information to adapt the absorption curves to other localities is detailed. It was determined that each kg of fresh fruit of Tommy Atkins and Keith, respectively, consumed 1.54 and 1.59 g K; 1.07 and 1.06 g N; 0.20 and 0.12 g P; 0.29 and 0.14 g Ca; 0.19 and 0.15 g Mg; 0.07 and 0.09 g of S; 8.5 and 2.5 mg Fe; 3.5 and 2.1 mg Mn; 0.7 and 1.6 mg B; 1.2 and 0.97 mg Zn; and 1.1 and 0.9 mg Cu. Also; appropriate stages are suggested for foliar fertilization and it was found that some nutrients shouldn’t be applied simultaneously, because of possible antagonisms. Field measurements (equatorial diameter and length) in both cultivars would be useful to establish the time of harvest; to obtain fruits of Tommy Atkins with fresh weight varying between 400 and 500 g, harvest should be performed when diameter fluctuates between 8.7 and 9.0 cm, or when length fluctuates between 10.7 and 11.2 cm. In the case of Keith, to obtain fruits with a harvest weight between 600 and 750 g, harvest must be done when average diameter varies between 9.4 and 9.8 cm or when length is between 13.5 and 14.0 cm, according to regression analysis.